If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 = -1(7 + -6r) 41 = (7 * -1 + -6r * -1) 41 = (-7 + 6r) Solving 41 = -7 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. 41 + -6r = -7 + 6r + -6r Combine like terms: 6r + -6r = 0 41 + -6r = -7 + 0 41 + -6r = -7 Add '-41' to each side of the equation. 41 + -41 + -6r = -7 + -41 Combine like terms: 41 + -41 = 0 0 + -6r = -7 + -41 -6r = -7 + -41 Combine like terms: -7 + -41 = -48 -6r = -48 Divide each side by '-6'. r = 8 Simplifying r = 8
| 10x-15=7+15 | | 5y+10=6+2y | | 5(35)=m | | 8y-12y=-19-25 | | 2(4x+7)=-50+48 | | ln(7x)=ln(x^2-18) | | 10u^2-1u-2=0 | | 15p^2+24p+8=0 | | 26-(x+7)=8x-8 | | 11/2*11/3*11/4= | | 2x-7=20x+2 | | 18.8=2*3.14r | | 6x-12=6x-12 | | x^2-6x+9=23 | | 2y-1=-5 | | 80a^4-280a^2+245= | | 3b^2-5b-2= | | x^2+10x-184=0 | | 0.83c+0.75=0.916 | | 30=7+12+c | | 3(2c-1)-2=2c+7 | | 4m+2(4-8m)=-64 | | 4=2x-3 | | 6-3(x+1)=-4(x+6)+2 | | 2x^2-32x+128=0 | | 2x^2y+3xy^2+y^3= | | 4(n-8)+4(n-6)=3n+1-2 | | 25x^2-30x=166 | | 3t-8=4(t+6) | | 12+9q=14+8q | | y^2-10y+50=0 | | 3m+2(2m+8)=8(m+2) |